Columnar-structured thermal barrier coatings deposited via the water-based suspension plasma spray process. (19th May 2022) - Xu, Pengyun; Meng, Guohui; Liu, Guijie; Coyle, Thomas; Pershin, Larry; Mostaghimi, Javad
Abstract: Suspension plasma spray (SPS) has been developed as a rapid, facile and cost-effective process to deposit columnar-structured thermal barrier coatings (TBCs). In contrast to the most commonly used ethanol-based suspensions, water-based suspensions have not been used in the SPS process to deposit columnar-structured TBCs due to their high surface tension, although they are much cheaper and safer. In this work, a new water-based SPS process was prepared by adding surfactant to lower the surface tension. The optimum content of dispersant and surfactant added to the suspension was determined via measurements of viscosity, particle size, surface tension, contact angles, and atomized droplet size. Coatings deposited using suspensions with and without surfactant showed typical columnar-structured microstructures and vertically cracked microstructures, respectively. The coatings deposited using suspensions with surfactant also showed evolution from columnar-structured microstructures to mixed microstructures of columns and cracks, and to homogeneous microstructures with the increase in standoff distance. The formation of different coating microstructures was correlated to the size of droplets after aerodynamic breakup and the Stokes number of in-flight particles. The new water-based suspension together with the water-based SPS process show great potential to be a cheap and effective alternative to the ethanol-based SPS process.